Predictors of frailty in old age: results of a longitudinal study - Hajek, André; Weyerer, Siegfried; Werle, Jochen (The journal of nutrition, health & aging, 2016)
OBJECTIVES: To investigate time-dependent predictors of frailty in old age longitudinally. DESIGN: Population-based prospective cohort study. SETTING: Elderly individuals were recruited via GP offices at six study centers in Germany. The course of frailty was observed over 1.5 years (follow up wave 4 and follow up wave 5). PARTICIPANTS: 1,602 individuals aged 80 years and older (mean age 85.4 years SD 3.2, with mean CSHA CFS 3.5 SD 1.6) at follow up wave 4. MEASUREMENTS: Frailty was assessed by using the Canadian Study of Health and Aging Clinical Frailty Scale (CSHA CFS), ranging from 1 (very fit) to 7 (severely frail). RESULTS: Fixed effects regressions revealed that frailty increased significantly with increasing age (β=.2) as well as the occurrence of depression (β=.5) and dementia (β=.8) in the total sample. Changes in marital status and comorbidity did not affect frailty. While the effects of depression and dementia were significant in women, these effects did not achieve statistical significance in men. CONCLUSION: Our findings highlight the role of aging as well as the occurrence of dementia and depression for frailty. Specifically, in order to delay frailty in old age, developing interventional strategies to prevent depression might be a fruitful approach.